A criança com transtorno do espectro autista na sala regular da educação infantil: das políticas educacionais às práticas pedagógicas em João Pessoa-PB - Santos, Isabelle Sercundes (2020)
This research discusses the policies of educational inclusion that guide the pedagogic process and practices developed in the context of Childhood Education focused on Autism Spectrum Disorder (ASD). In this sense, our general aim is to understand to which extent the children educational inclusion with ASD is fulfilled. To such, we limit the following specific aims: a) Investigating the nature of the educational process involved in children with ASD; b) Reflecting about the advances and challenges that unfold from the legal guidelines that guide the insertion of children with ASD in Childhood Education. The theoretical framework is based on the postulations of scholars that approach these questions mentioned above. The study has a qualitative focus with an exploratory research, involving documental and empiric researches. Our techniques were data collect from deep semi-structured interviews and participating observations. The Dialectical Hermeneutics with the contributions of the Cultural-Historical Theory was the method that conducted the rationale to understand the studied reality. Our research locus was a Centre for Reference in Childhood Education (CREI, abbreviation in Portuguese), in João Pessoa, Paraiba, Brazil. Our research’s individuals involved 6 children with ASD, 2 in-service teachers, 5 caretakers, 1 head teacher, 1 supervisor, 1 teacher from the Specialized Educational Service and 5 mothers, making a total sum of 21 individuals. The main results pointed out that the pedagogical practices to children inclusion with ASD demand a systematization that give more opportunity to those children and that take into consideration curriculum adaptation in accordance with their needs in order to foster learning and development in regular classrooms. At last, one concludes that the educational policies of inclusion advanced substantially in the local and national context, bringing material resources and professional help to let environments and information more accessible, which has enlarged progressively the presence of children with special needs at public schools. However, in dealing with the public of early childhood with ASD, some improvements are in demand, such as in-depth ongoing trainings that tackle the inclusion; making experts a priority in the monitoring of children in regular classrooms; and the investment in materials, time frames and environments that allow to play, to learn and to develop oneself at the most.